Role of Ponseti Technique in Late Presenting and Relapsed Idiopathic Congenital Talipes Equinocavo Varus Feets – Our Experience - Patil, Naveenkumar (Journal of Neonatal Surgery, 2025)
Objectives: Idiopathic Congenital Talipes Equino Varus (CTEV), commonly referred to as Clubfoot, is a complex musculoskeletal deformity affecting infants. The Ponseti technique, a gold standard approach, has emerged as an effective treatment. This study aims to evaluate the clinical outcomes of ponseti technique in children with idiopathic clubfoot who presents late after 03 months of birth and in relapsed infants up to one year of age. Methods: A prospective study was conducted at the Department of Orthopaedics, involving 41 feet. Infants with idiopathic clubfoot were included. Infants started on ponseti treatment with serial castings followed by percutaneous tendo Achilles tenotomy corrections were monitored by scoring systems, Paired samples ‘T’ was applied for statistical analysis. The statistical difference was considered to be significant when P <0.05 and highly significant when P < 0.001. Correlation between different parameters was analyzed by Spearman correlation coefficient. Results: we treated 29 cases (41 feet) of idiopathic clubfoot in children more than three months. Age group classification was: group 1 (3 to 5 months), group 2(6 to 9 months) , group 3 (10 to 12 months) and group 4 (> 12 months). In group 1 mean pre Pirani and Dimeglio scores were higher than group 4, reduction of scores after corrective casting were more statistically significant in group 1 than group 2,3,4. This suggests that the Ponseti technique is effective in older age group but the effectiveness decreases as the age increases. Conclusion : Thus Ponseti technique safe, effective and can be used as preferred initial treatment for congenital idiopathic clubfoot in patients presenting late, irrespective of age and initial severity , avoiding the need for extensive surgery later